Pengaruh Pemberian Insentif, Pelatihan Kerja dan Pengendalian Intern terhadap Efektivitas Kinerja Karyawan - Heni Risnawati; Sri Retnoningsih (Faculty of Economics and Business, University of Pancasakti Tegal, 2020)
The purpose of this study to determine the effect of providing incentives, job training and internal control on the employee performance of RSUD RAA Soewondo Pati Hospital. The population in this study is employees of the RSUD RAA Soewondo Pati Hospital. The number of samples used in this study is 235 medical and non medical employees. The analytical tool used by authors is multiple linear regression analysis to analyze the research data. The partial results of the first hypothesis of incentives do not significantly influence employee performance. That is because there are still some employees who are not satisfied with the system of providing incentives. The second hypothesis shows that job training does not significantly influence employee performance. This means that job training at the hospital is still less effective in improving performance. The third hypothesis shows that internal control has a significant positive effect on employee performance. Existing internal control at the hospital is going well in improving employee performance. The simultan research provides empirical evidence that the provision of incentives, job training and internal control together a significant effect on the employee performance of RSUD RAA Soewondo Pati Hospital.